Facile Pathways to Synthesize Perovskite Strontium Cobalt Oxides. (11th November 2022) - Lu, Sicheng; Yin, Fang; Wang, Yujia; Lu, Nianpeng; Gao, Lei; Peng, Huining; Lyu, Yingjie; Long, Youwen; Li, Jia; Yu, Pu
Abstract: Topotactic phase transition obtains extensive research attention due to its associated rich physics as well as a promising potential application. Particularly, the oxygen incorporation into brownmillerite oxides leads to the structural transition into perovskite oxides with distinct magnetic and electronic properties. Using brownmillerite SrCoO2.5 (BM‐SCO), two novel pathways are revealed to achieve the topotactic phase transition into its corresponding perovskite SrCoO3 (P‐SCO). It is demonstrated that by using aqueous alkali as the electrolyte during gating, the negative biased voltage triggers a rapid transition into P‐SCO, which is attributed to the presence of strong oxidizing hydroxyl radicals. While surprisingly, it is observed that the acid solution with rich protons can also trigger an unexpected phase transition from BM‐SCO into P‐SCO in a much faster manner. With density functional theory calculations, this transition is elucidated as a proton‐assist ionic disproportionation, in which the Co ions are simultaneously oxidized and reduced, while the latter one is dissolved within the solution. These case studies not only achieve a deep understanding of the structural phase transition in BM‐SCO but also shed new light on the topotactic phase transition of complex oxides. Abstract : Topotactic phase transition from brownmillerite SrCoO2.5 (BM‐SCO) to perovskite SrCoO3 (P‐SCO) obtains extensive research attention due to its distinct magnetic and electronic properties as well as a promising potential application. This study demonstrates two novel facile pathways with rapid phase transition rates to obtain P‐SCO, the aqueous alkali gating, and acid solution reaction methods, and the underlying mechanisms are also carefully explored. Not only a deep understanding of the structural phase transition in BM‐SCO is offered but also new light is shed on the topotactic phase transition of complex oxides.